1997
DOI: 10.1590/s0103-50531997000200016
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical study of charge transfer in conducting polymers

Abstract: Aspectos cinético e termodinâmico da transferência de carga em polímeros condutores foram investigados. Um modelo de difusão restrita foi impregado para interpretar os da dos obtidos por cronopotenciometria com pulso. Em filmes de poli 3-metiltiofeno, o coeficiente de difusão aparente diminuiu em função da espessura do filme mas ficou constante com a concentração eletrolítica. Em filmes finos, usando-se voltametria cíclica, caracterizou-se mudanças termodinâmicas, como em par tic u lar, a deconvolução das duas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Some studies concluded that the ionic diffusion coefficient decreases with the thickness of the polymer film, and it is slightly influenced by the electrolyte concentration. Focusing on the cationic doping of Ppy, it was possible to observe a change in the diffusion speed as a function of the ionic radius of the dopant [ 83 ]. Such a conclusion was obtained despite different polymerization methods, namely, galvanostatic, potentiostatic, and potentiodynamic, being applied for Ppy layer production.…”
Section: Design Aspects Of Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies concluded that the ionic diffusion coefficient decreases with the thickness of the polymer film, and it is slightly influenced by the electrolyte concentration. Focusing on the cationic doping of Ppy, it was possible to observe a change in the diffusion speed as a function of the ionic radius of the dopant [ 83 ]. Such a conclusion was obtained despite different polymerization methods, namely, galvanostatic, potentiostatic, and potentiodynamic, being applied for Ppy layer production.…”
Section: Design Aspects Of Sensorsmentioning
confidence: 99%
“…Pulsed current polymerization undoubtedly leads to more compact and adherent films. It was found that the reversibility of the redox process of the films decreased, and the thickness could not be simply related to the polymerization charge [ 83 ]. This observation is very important for different applications of conducting polymers, especially for sensors, where a thin and compact layer of polymer is needed.…”
Section: Design Aspects Of Sensorsmentioning
confidence: 99%
“…Ilustra-se a seguir, na Figura 4, o efeito de K 0 sobre a reversibilidade um processo quasi-reversível. partir dos dados voltamétricos obtidos à baixa velocidade de varredura de potencial 14 , os dados cronopotenciométricos podem ser ajustados usando-se as equações acima, o que permite a determinação de D ap .…”
Section: Reação Quase-reversívelunclassified
“…Several attempts exist for the description of voltammetric responses to cyclic potential sweeps or for chronoamperometric responses to potential steps. Chronopotentiometric responses have been modeled from impedance results using equivalent electrical circuits. , As far as we know, only Micka et al tried to propose a self-supporting model (without adjustable parameters) for polyacetylene oxidation based on the empirical dependence of the electrical conductivity and the stationary potential on the degree of doping, not considering experimental chemical variables. The evolution of the potential at open circuit was studied by Pernaut et al employing pulse chronopotentiometric experiments and concepts from diffusion …”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the potential at open circuit was studied by Pernaut et al employing pulse chronopotentiometric experiments and concepts from diffusion. 63 In this paper we propose an initial physicochemical approach to the description of the actuating-sensing properties of conducting polymers, materials, and devices, working under galvanostatic control. Theoretical and experimental results will be presented for self-supported polypyrrole responses at different temperatures and compared with those existing for artificial muscles sensing temperature (the actuator, an artificial muscle, sense ambient temperature) while working.…”
Section: ■ Introductionmentioning
confidence: 99%